2015
DOI: 10.1088/0957-4484/26/31/315202
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and photocurrent from InP nanowires with InAsP quantum dots grown on Si by molecular beam epitaxy

Abstract: InP nanowires with InAsP quantum dots (QDs) were grown by molecular beam epitaxy on a Si (111) substrates. The structure of the InAsP QDs were studied using transmission electron microscopy, allowing the development of a model where QD growth occurs by group V desorption from the surrounding substrate surface. Micro-photoluminescence was performed at 10 K showing emission at 1.47-1.49 eV from the InP wurtzite structure, and various emission peaks between 0.93 and 1.33 eV attributed to the QDs. The emission was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
1
21
1
2
Order By: Relevance
“…7,53,54 The main purposes for growing these heterostructures ranges from creating a transition from a substrate material into a desired active device material, 48 creating an active part of a device by promoting tunnelling at a staggered bandgap heterostructure interface 55 or for creating quantized structures used in for example infrared photodetectors (see Figure 1i−m). 53,54,56 However, when growing ternary alloy materials such as In x Ga 1−x As and In x Ga 1−x P, where alloy mixing occurs on the group III sublattice, it is important to consider the implications the growth will have on the full 3-D NW structure. For example, it has been observed that composition can vary in the axial 51,52 as well as the radial direction 35 due to the difference in group III adatom diffusion lengths.…”
Section: Iii−v Nanowire Growth Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,53,54 The main purposes for growing these heterostructures ranges from creating a transition from a substrate material into a desired active device material, 48 creating an active part of a device by promoting tunnelling at a staggered bandgap heterostructure interface 55 or for creating quantized structures used in for example infrared photodetectors (see Figure 1i−m). 53,54,56 However, when growing ternary alloy materials such as In x Ga 1−x As and In x Ga 1−x P, where alloy mixing occurs on the group III sublattice, it is important to consider the implications the growth will have on the full 3-D NW structure. For example, it has been observed that composition can vary in the axial 51,52 as well as the radial direction 35 due to the difference in group III adatom diffusion lengths.…”
Section: Iii−v Nanowire Growth Methodsmentioning
confidence: 99%
“…The axial NW heterostructure has been regarded as one of the key benefits of NWs compared to planar layers because strain can be elastically relaxed via the free surfaces, thus reducing defects such as dislocations when there is a lattice mismatch. Although the flexibility even for axial heterostructures is not endless and misfit dislocations eventually will form, there are unique possibilities for new defect-free material combinations compared to planar growth such as InAs-InSb, GaAs-GaSb, InAs-GaSb, GaAs-InAs, GaAs-InGaAs, InP-InGaP, GaP-InGaP, and InAsP-InP. ,, The main purposes for growing these heterostructures ranges from creating a transition from a substrate material into a desired active device material, creating an active part of a device by promoting tunnelling at a staggered bandgap heterostructure interface or for creating quantized structures used in for example infrared photodetectors (see Figure i–m). ,, However, when growing ternary alloy materials such as In x Ga 1– x As and In x Ga 1– x P, where alloy mixing occurs on the group III sublattice, it is important to consider the implications the growth will have on the full 3-D NW structure. For example, it has been observed that composition can vary in the axial , as well as the radial direction due to the difference in group III adatom diffusion lengths.…”
Section: Iii–v Nanowire Growth and Devicesmentioning
confidence: 99%
“…The use of cheap silicon-based substrates allows the integration of III-V-based devices as single-photon sources and photodetectors. 1 However, the integration of III-V semiconductors on the silicon substrate presents a technological challenge due to the higher dislocation defects related to the large lattice mismatch between silicon and the most III-V materials. They also exhibit significant stress caused by the large differences in thermal expansion coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]. Особый интерес представляет возможность создания гетероструктур типа нановставка (или квантовая точка) в теле ННК с большей шириной запрещенной зоны, что позволяет расширять диапазон излучения ННК, получать источники одиночных фотонов, формировать направленные источники излучения [5][6][7][8]. Однако полупроводниковые нанокристаллы часто характеризуются сложной динамикой возбужденного состояния.…”
Section: Introductionunclassified